Air pollution and the development of respiratory diseases in the pediatric age: a scoping review (Epidemiology, Biostatistics, and Public Health, 2025)
Introduction: Pollution presents a significant danger, especially for children's health since they are more vulnerable to respiratory infections. In low-income countries many diseases result from limited access to health services and poor sanitary conditions, and this associated with exposure to pollutants makes it a relevant issue for public health. This article synthesizes the evidence on the effects of air pollution on respiratory diseases in early childhood. Materials and Methods: A scoping review was conducted consulting PUBMED, LILACS, and Medline databases, with studies from 2013 to 2024. A total of 22 articles were used for the present review. Results: The relevance of PM2.5 and other pollutants such as PM2.5, PM10, NO3 was highlighted, being associated with acute (cough, wheezing, pneumoniae) and chronic respiratory diseases (rhinitis, asthma), affecting lung function during lifetime. In addition, the association between pollution, social determinants, genetics, and prenatal development on child health outcomes was depicted. Discussion: the review highlights that PM2.5 exposure is significantly linked to adverse respiratory outcomes in children and recognizes limitations such as language and database restrictions that might introduce bias. Additional socioeconomic factors like financial stability and literacy also play a role in respiratory health outcomes. Conclusion: It is imperative to formulate public health policies to address this problem from an interdisciplinary point of view, giving an adequate approach to the different factors that influence the development of respiratory infections in early childhood, especially pollution.
Keywords: air pollution; Respiratory system diseases; asthma; wheezing; children